Analisis Sistem Pembiayaan Pendidikan yang dikelola Kementerian Agama - M. Hanif Satria Budi (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
Education financing system is very important in educational institutions. Starting from elementary level education to higher education. The policy in making this financing system a duty and responsibility of the relevant institutions. The Ministry of Religion that supports madrassas and universities such as UIN, IAIN, STAIN and other private universities also has its own education funding system. This financing system is important so that distribution is equitable and fair. This study uses the Library Research Approach for the strategic planning analysis of the Ministry of Religion and the Foundation for education financing policies.